Harmony in nature: understanding the cultural and ecological aspects of plant use in Ladakh - Kunzes Angmo; Bhupendra S. Adhikari; Rainer W. Bussmann; Gopal S. Rawat (BMC, 2024)
Abstract Background Traditional knowledge (TK) in Ladakh encapsulates a repository of experimental wisdom cultivated over millennia. Despite this cultural wealth, dwindling interest among the younger generations in the region's age-old practices underscores the urgency to document TK. The current study investigates the diverse usage of plants in Surru, Wakha and Lower Indus valleys of Western Ladakh exploring the influence of socioeconomic and ecological factors. Methods A stratified random sample approach was adopted to select 540 respondents for gathering information of useful plants through interviews and questionnaires. Participant observation, questionnaires, open-ended and semi-structured interviews were conducted for data collection. Free listing was done to create an extensive list of plants and their uses. Ethnobotanical metrics such as relative frequency of citation (RFC), relative importance index (RI), cultural value (CV) index and cultural importance (CI) index were computed to assess species applicability. Additionally, one-way analysis of variance (ANOVA) was utilized to discern significant differences in knowledge levels based on valleys, gender, education and religion using TK as a response variable. Results Altogether, we recorded 246 plant species under various ethnobotanical uses from Western Ladakh. These include medicinal (126), fodder (124), wild ornamentals (86), food (81), fuel wood (54), dye (20), religious (31) and others (34). Novel plant reports include Berberis brandisiana Ahrendt and Dactylorhiza kafiriana Renz. The dominant plant family is Asteraceae with 35 species. Suru valley exhibits the highest number of cited plants followed by Wakha-chu and Lower Indus valleys (192, 168 and 152 species, respectively). Conclusion Disparities in plant use understanding are evident among different groups, prompting further investigation through intercultural comparisons. Plants such as Arnebia euchroma, Juniperus semiglobosa, and Artemisia species emerge with cultural importance. Gender, valley affiliation, religious background and the remoteness of a village all influence local plant knowledge. These variations are linked to socioeconomic disparities among communities.